Effect Digital Marketing and Influencer Endorsment of the Decission of the Purchase of Products Scarlett Whitening (Case Study the Students STIE Eben Haezer Manado) - Rondonuwu, Theressa; Dyrgo, Hongky; Mumu, Sweetly (PT FORMOSA CENDEKIA GLOBAL, 2025)
In the digital age, technology affects all aspects of life, including marketing. The digital age gives marketers a new perspective and makes it easier to learn about consumer-friendly products, brands, strategies and services. Digitalization enables personal communication and reaches large groups of consumers. It helps with online advertising, video sharing, mobile phones, web apps and online services. This research investigates the impact of digital marketing and influencer endorsement on the acquisition of Scarlett Whitening products. The analysis use multiple linear regression. Digital marketing exerts minimal influence on consumer purchasing decisions for Scarlett Whitening, as other factors, including unsuitable products and strategies, must be taken into account. Conversely, influencer endorsement significantly impacts consumer awareness, as testimonials from influencers effectively convey that Scarlett Whitening is the superior product.